2017
DOI: 10.1016/j.foodres.2017.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of in vitro gastrointestinal digestion on the bioaccessibility of phenolic compounds, minerals, and antioxidant capacity of Mimosa scabrella Bentham honeydew honeys

Abstract: Honey is a product traditionally consumed due to its possible health benefits promoted by natural antioxidants. However, few studies have evaluated the effect of in vitro gastrointestinal digestion on these compounds in honeys. To improve the knowledge of this subject, the present study aimed to investigate the influence of simulated digestion on the stability of antioxidant capacity (FRAP, DPPH, and Folin-Ciocalteu assays), phenolic compounds (LC-ESI-MS/MS), and minerals (CE-DAD) in Mimosa scabrella Bentham h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 53 publications
5
56
1
7
Order By: Relevance
“…As shown in the table, phenolic acids appear to be more stable during the gastrointestinal digestion process; in particular, they show that 3,4 dihydroxybenzoic acid maintains approximately the same quantities in the digested sample. As for the other phenolic acids present, such as ferulic acid, p-coumaric acid and syringic acid, there was a decrease in the bioaccessible fraction, but salicylic acid's (SA) intestinal fraction increased from 42.40 µg/kg honey in MH to 56.23 in DMH, as reported in other works [27]. This result could be due to the demethylation processes of methyl salicylate enzymes, widely present in raw honey, and because these phenolic acids could be linked to other molecules such as sugars, that protect them during the digestion process [28].…”
Section: Phenolic Profiling By Hplc-esi-ms/mssupporting
confidence: 82%
See 1 more Smart Citation
“…As shown in the table, phenolic acids appear to be more stable during the gastrointestinal digestion process; in particular, they show that 3,4 dihydroxybenzoic acid maintains approximately the same quantities in the digested sample. As for the other phenolic acids present, such as ferulic acid, p-coumaric acid and syringic acid, there was a decrease in the bioaccessible fraction, but salicylic acid's (SA) intestinal fraction increased from 42.40 µg/kg honey in MH to 56.23 in DMH, as reported in other works [27]. This result could be due to the demethylation processes of methyl salicylate enzymes, widely present in raw honey, and because these phenolic acids could be linked to other molecules such as sugars, that protect them during the digestion process [28].…”
Section: Phenolic Profiling By Hplc-esi-ms/mssupporting
confidence: 82%
“…The TAC in MH, evaluated with FRAP and TEAC, was 261.73 and 251.89 µmol TEq/100 g honey, respectively, and was lowered in the sample representing the bioaccessible intestinal fraction to values of 119.81 and 114.67, respectively. The DPPH test, as in the studies of O'Sullivan et al [16] and Seraglio et al [27], showed a greater decrease in the undigested and the digested sample, suggesting that it is more specific to phenolic compounds than the other two methods used. In fact, the TAC value obtained from the MH (86.479 µmol TEq/100 g honey) decreased by approximately seven times (11.8214 µmol TEq/100 g honey) in DMH as the trend ofTPC and TFC.…”
Section: Total Phenolic Compounds and Antioxidant Activitymentioning
confidence: 88%
“…Based on the electrical conductivity of the 28 honey samples, eight samples belong to the group of honeydew honey, marked as No. 1,3,4,7,8,16,25,26 (Fig. 1).…”
Section: Honey Classicationmentioning
confidence: 95%
“…Some studies have shown appreciably higher content of bioactive compounds for honeydew honey that causes its higher antioxidant activity. [2][3][4][5] These higher values point to more therapeutic properties of honeydew honey, which give a rise to its commercial interest. The demand for honeydew honey is increasing, especially in certain regions of Europe where consumers enjoy its remarkable avor.…”
Section: Introductionmentioning
confidence: 99%
“…Still, during these months the production of this specific type of honey is favoured because this period coincides with the low availability of flowers, causing the bee to use the exudate to produce honey (Mazuchowski et al 2014). Although its properties have not yet been well elucidated, it is recognized that Bracatinga honeydew honey possesses unique nutritional properties, such as free amino acids (Azevedo et al 2017) and bioaccessible amounts of minerals and phenolic compounds (Seraglio et al 2017).…”
Section: Introductionmentioning
confidence: 99%